Analisis Penerapan Doktrin Business Judgment Rule Terhadap Keputusan Direktur Utama PT Krakatau Steel Tbk Dalam Kasus Pembangunan Blast Furnace Complex - Anindita Maharani; Nadya Hanifah; Nyulistiowati Suryanti; Deviana Yuanitasari (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
In business activities in the form of a Company, there are often legal problems involving directors as a result of the decisions and policies they make in carrying out their duties and authority in the company. The Board of Directors is one of the most important organs in a Limited Liability Company whose duty is to run the company as stated in Law Number 40 of 2007 (UU PT) concerning Limited Liability Companies. In the event of a loss caused by the decision or policy, the board of directors can be sued personally either criminally or civilly. This research aims to analyze the case of former President Director of PT Krakatau Steel (KS) Fazwar Bujang in making decisions on the construction of the Blast Furnace Complex plant in 2011 which is considered to have harmed the state of Rp 2.3 trillion and USD 292 or up to Rp 6 trillion and has benefited the MCC Ceri consortium, a company from China and PT Krakatau Engineering and others. The first result shows that the business judgment rule doctrine is a concept in corporate law that provides protection to company directors regarding the decisions and policies they make, to ensure that directors can make decisions based on good faith, prudence, and the best interests of the company without having to be personally liable for losses that may arise from business decisions. In Indonesia, the business judgment rule doctrine is only regulated in UU PT, but it has not been regulated in the law completely. Second, in the case of the construction of PT Krakatau Steel's Blast Furnace Complex, the business judgment rule cannot be applied because the business policies taken do not meet the requirements of the business judgment rule stipulated in Article 97 paragraph (3) of the UU PT.